PEMETAAN MELALUI FOTO UDARA PADA LAHAN MARGINAL (TIDUR) YANG BERPOTENSI UNTUK DIJADIKAN LAHAN PERKEBUNAN DI DESA BINAMANG, KECAMATAN XIII KOTO KAMPAR, KABUPATEN KAMPAR, PROVINSI RIAU - Nazaruddin; Kaspul Anuar; Warman Fatra; Awaludin Martin; Asral (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
The area of ​​Binamang Village has potential area to develop its plantation. Besides being suitable for planting oil palm and rubber commodities, Binamang village is also suitable to be developed by its plantations in the commodities of brown, gambier and gaharu. This is also supported by the large amount of marginal (non productif) land that has not been used in the village of Binamang. However, some of these marginal area are the Koto Panjang PLTA lake catchment area. Clear and detailed mapping is need to classify of marginal area which is potential to be used as plantation land in this area. This is done so that there will be no conflicts in the future. In addition, this mapping data is also useful as information data for potential investors who intend to invest their funds in the plantation sector in Binamang Village. To classify the marginal area which is not the Koto Panjang hydropower (PLTA) lake catchment area, a team of lecturers from the Mechanical Engineering Department of the University of Riau carried out community service activities in the village of Binamang, in the form of build maps of marginal area that could potentially be used as plantation / agriculture. This map is equipped with a geospatial information system. This mapping activity was carried out by using aerial photographing methods through Unmanned Aircraft by involving students of Riau University and local village equipment. This aerial photography activity is carried out at an altitude of 250 meters above ground level. With this method, all marginal areas in Binamang village can be mapped quickly and in detail. Based on calculations carried out through aerial photographic maps that have been injected with GPS coordinates, the marginal area that has the potential to be developed into plantations in Binamang Village is about 40 hectares. This result can be a reference for relevant stakeholders in planning the development of plantation areas in Binamang Village. The results of aerial maps can also be used by local policy makers in planning the spatial layout of Binamang Village.